The Unexpected Consequences of Job Search Monitoring: Disability Instead of Employment? - Octave De Brouwer; Elisabeth Leduc; Ilan Tojerow (Institute of Labor Economics (IZA), 2019)
This paper investigates how the implementation of Job Search Monitoring (JSM) programs over the last two decades could have impacted the rise of disability rates in OECD countries. To do so, we use an RDD design to study how a JSM program that was implemented in 2006 in Belgium could have played a role not only in the transition to employment and inactivity but also in the transition to disability. The RDD exploits the fact that the program was only targeted at long-term unemployed workers below the age of 50. Our results show that the JSM program has had a large impact on the transition rate from unemployment to disability and no impact on the transition rate to employment or inactivity. More precisely, individuals just below the age of 50 (the treatment group) are 1.43 percentage points (115%) more likely than individuals just above the age cut-off (the control group) to enter into disability during the next quarter. Looking at heterogeneous effects, we find that the effect is above all important for women and more particularly for single-women households. Overall, our study shows that JSM programs can have spillover effects on other social security branches, such as work disability. This is an important concern since it implies that JSM programs can push some individuals even further away from the labour market. Finally, our results show that the implementation of JSM could, constitute a viable explanation for the rise of the disability rate amongst unemployed workers.
Keywords: I13; J64; 330; disability; unemployment; Job Search Monitoring